Fishing in the Kama River Area in the Sources of 1720–1780 - А. А. Kosmovskaya (Вестник Кемеровского государственного университета, 2020)
The research was based on previously unpublished financial documents of the Solikamsk and Kungursk provincial archives. The research featured income from fishing lease in the Kama River Area in 1720-1780. The geographic features of the region determined the distribution of fishing areas. The role of provincial offices (voivodships) in collecting fishing leases in this territory is new to historiography, as well as the issue of the fishing quota and the lease volume. The author made an attempt to estimate the size of revenues from the fishing industry for the population of the Kama region in the XVIII century. The low fees revealed that the fish lease played a minor role in the general structure of tax revenues. The study of various financial documents made it possible to describe the local fishing industry, the amount of fishing fees, and the social structure of leasers, who were free peasants and factory workers. As a rule, the rent hardly changed during the period and rarely exceeded 1 ruble for a fishing area per year.